THE ROLE OF NEUTROPHIL/HIGH DENSITY LIPOPROTEIN, MONOCYTE/HIGH DENSITY LIPOPROTEIN AND LOW DENSITY LIPOPROTEIN/HIGH DENSITY LIPOPROTEIN RATIOS IN DETERMINING THE PRESENCE AND SEVERITY OF ASYMPTOMATIC CAROTID STENOSIS IN ELDERLY PERSONS - Bolayir, Asli; Bolayır, Hasan Ata (My University, 2021)
INTRODUCTION: The importance of the lipid-related biomarkers, like neutrophil to high density lipoprotein cholesterol\r(HDL) ratio (NHR), monocyte to HDL ratio (MHR) and low density lipoprotein cholesterol (LDL) to HDL ratio (LHR), has\rbeen implicated in the pathological process of atherosclerosis. Our study was conducted to discuss and compare the\rpredictive ability of the NHR, MHR and LHR in elderly patients with asymptomatic carotid stenosis(ACS).\rMETHODS: Our study included 124 patients, aged ? 65 years, complained with dizziness and applied to our clinic from\rJanuary 2010 to September 2020 and 125 healthy controls of similar age and gender. When blood samples were taken for\rwhite blood cell count and biochemical analysis; carotid artery Doppler ultrasonography was performed to define carotid\rstenosis.\rRESULTS: While NHR, MHR and LHR values were significantly higher in the patient group; a linear correlation was found\rbetween NHR, MHR and LHR values and the degree of carotid stenosis. In the ROC analysis performed to determine the\rcut-off values in detecting carotid stenosis, the area under the curve (AUC) for NHR was 0.68 and the cut-off point was\r0.09; the AUC for MHR was 0.61, cut-off point was 0.01 and the AUC for LHR was 0.58 and the cut-off point was 1.61.\rDISCUSSION AND CONCLUSION: As a result, we revealed that NHR, MHR, and LHR ratios can be used with a higher\rsensitivity than using these values individually in detecting asymptomatic carotid stenosis in elderly patients. In addition,\rNHR value was found to be a more valuable biomarker in defining the presence and degree of carotid stenosis compared\rto MHR and LHR values.
Keywords: Genel ve Dahili Tıp; Patoloji; Kalp ve Kalp Damar Sistemi